Two new self-adaptive algorithms for solving the split common null point problem with multiple output sets in Hilbert spaces - Reich, Simeon; Tuyen, Truong Minh (Fixed point theory and algorithms for sciences and engineering, 2021)
To solve the split common null point problem with multiple output sets in Hilbert spaces, we introduce two new self-adaptive algorithms and prove strong convergence theorems for both of them.